Abusive Behavior of Parents and the Consequences on the Child - Giurgea, Lenuta (Acta Universitatis Danubius. Juridica, 2022)
In the context of today's society, the family is an open system for rapid and major change. The purpose of the family is to provide for the needs of its members. Both parents have well-established roles in the organizational framework. The rights between parents and children are the same between the two parties. The major role of parents is to ensure a balanced educational and emotional climate within the family. Because of the tense situations between the two parents, the balance is destroyed, and the consequence of this is a trauma for the children, be it mental or even physical sometimes. The tensions arising within the family or between ex-spouses, managed in a deficient and selfish way, mark not only the present child but also the future adult.